2005
DOI: 10.1037/h0087476
|View full text |Cite
|
Sign up to set email alerts
|

Eye Movements and Phonological Parafoveal Preview: Effects of Reading Skill.

Abstract: Eye movements of skilled and less skilled readers were monitored as they read sentences containing a target word. The boundary paradigm was used such that when their eyes crossed an invisible boundary location, a preview word changed to the target word. The preview could either be identical to the target word (beach as a preview for beach), a homophone of the target word (beech as a preview for beach), an orthographic control (bench as a preview for beach), or an unrelated consonant string (jfzrp as a preview … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
108
1
4

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 137 publications
(127 citation statements)
references
References 14 publications
13
108
1
4
Order By: Relevance
“…Our finding that parafoveal information speeded silent reading more for faster readers than for slower readers is consistent with Rayner et al (2010) and with Chace, Rayner, and Well (2005). The latter study reported larger parafoveal phonological effects for more skilled readers than for less skilled readers.…”
Section: Discussionsupporting
confidence: 80%
“…Our finding that parafoveal information speeded silent reading more for faster readers than for slower readers is consistent with Rayner et al (2010) and with Chace, Rayner, and Well (2005). The latter study reported larger parafoveal phonological effects for more skilled readers than for less skilled readers.…”
Section: Discussionsupporting
confidence: 80%
“…These observations were further reinforced by correlational analyses and RT distributional analyses. The present results add to a growing body of literature demonstrating the impact of individual differences in reading skills on the different stages of word processing (see Chace, Rayner, & Well, 2005;Häikiö et al, 2009;Janack, Pastizzo, & Feldman, 2004;Rayner, Slattery, & Bélanger, 2010;Yap, Tse, & Balota, 2009;Ziegler, Jacobs, & Klüppel, 2001, to cite just a few examples). Of particular interest is the recent study by Andrews and Lo (2013), in which the participants' reading "profiles" (orthographic vs. semantic) modulated the , respectively) for the whole set of participants as a function of the participants' mean reaction times (RTs) in the lexical decision task magnitude of masked morphological priming effects-in particular, for morphologically opaque relationships (e.g., corner-CORN).…”
Section: Discussionsupporting
confidence: 71%
“…Furthermore, we must keep in mind that, during normal silent reading, phonological codes are used to integrate information across consecutive saccades (see Chace et al, 2005;Miellet & Sparrow, 2004;Pollatsek et al, 1992;Tsai et al, 2004). One might wonder, however, whether there is a high degree of phonological involvement in reading Japanese sentences.…”
Section: Discussionmentioning
confidence: 99%
“…Pollatsek and colleagues found that the fixation times on a target word (e.g., beach) were shorter when the parafoveal preview was a homophonic word (beech) than when it was a nonhomophonic control word (bench) (see also Chace, Rayner & Well, 2005, Miellet & Sparrow, 2004, and Tsai, Lee, Tzeng, Hung, & Yen, 2004, for replications in English, French, and Chinese, respectively). These findings strongly suggest that readers employ phonological codes to integrate information across consecutive saccades.…”
mentioning
confidence: 99%